The perspectives of unconscious winning myths in sports coaching. - Omar Fauzee, Mohd. Sofian; Yusof, Aminuddin; Jamalis, Marjohan (2008)
The purpose of this paper is to identify and critically discussed the ten pre-eminent unconscious winning myths that seldom realized by coaches, which are that: 1)The power and knowledge of coaches is all; 2)Experience is everything; 3)The motivator is the one we want; 4)Media representations are taken out of all proportion; 5)Physical and tactical skills are more than enough; 6)Winning is not everything but the only thing; 7)A good player is a good coach; 8)The champions are always right; 9)I know who I am; and 10)This is our culture and we don’t need to change anything. Perhaps by understanding the affect of these myths will helps sports coaches understand that to win athletes need to change their mind-set into more positive ways.